Experimental Study on Bearing Capacity of Normal- and High-Strength Steel Screw Anchors - Guodong Shao; Xiao Lyu; Wenming Wang; Shijun Ding; Jing Li; Mintao Ding; Hanke Sheng (Advances in Civil Engineering)
In order to study the bearing capacity of high-strength steel screw anchors, six groups of screw anchors with different parameters are carried out in in situ construction and tensile capacity test, and the load-displacement curves of screw anchors with different parameters are obtained. The bearing mechanism, design method, and key design parameters of screw anchors are analyzed. Meanwhile, the test results are compared with theoretical calculation and numerical simulation, respectively. The results show that the drawing capacity of high-strength screw anchor calculated by the existing standard theoretical calculation formula is conservative. The load capacity of high-strength steel screw anchor is significantly higher than that of ordinary strength steel screw anchor. Taking steel strength, buried depth, quantity, distance, and diameter as the influencing factors, parametric analysis is conducted on the uplift capacity of high-strength steel screw anchor in this paper. The embedding depth of screw anchor, the number, spacing, and diameter of anchor plates have significant influence on the drawing capacity of screw anchor. The construction technology of high-strength steel screw anchor is reliable, and the bearing capacity is good, which can be applied in the soft-soil power transmission line projects, such as bog and coastal beach. Meanwhile, the research results can provide reference for the design and construction of screw anchor foundation.